Prolonged Indwelling Urethral Catheterization as Minimally Invasive Approach for Definitive Treatment of Posterior Urethral Valves in Unstable Premature Babies - Silvia Ceccanti; Daniela Pepino; Antonella Giancotti; Ester Ricci; Silvia Piacenti; Denis A. Cozzi (Children, 2021)
Premature newborns with posterior urethral valves (PUV) may present with medical conditions taking priority over definitive surgical care. We encountered three of such cases who underwent initial bladder decompression via transurethral catheterization and waited 2–3 weeks until they were fit enough for voiding cysto-urethrography to confirm PUV. An unexpected good urinary flow and negligible residual urine volume were documented during micturition, suggestive of valve disruption induced by insertion and prolonged duration of indwelling urethral catheter drainage. Cystoscopy documented non-obstructing remnant leaflets. Non-operative treatment may be considered as a viable alternative therapeutic option for PUV in tiny babies facing prolonged intensive care unit stay.